A simplified model for equilibrium and transient swelling of thermo-responsive gels. (November 2017) - Drozdov, A.D.; deClaville Christiansen, J.
Abstract: A simplified model is developed for the elastic response of thermo-responsive gels subjected to swelling under an arbitrary deformation with finite strains. The constitutive equations involve five adjustable parameters that are determined by fitting observations in equilibrium water uptake tests and T -jump transient tests on thin gel disks. Two scenarios for water release under heating are revealed by means of numerical simulation. When the final temperature in a T -jump test is below the volume-phase transition temperature, deswelling is characterized by smooth distribution of water molecules and small tensile stresses. When the final temperature exceeds the critical temperature, a gel disk is split into three regions (central part with a high concentration of water molecules and two domains near the boundaries with low water content) separated by sharp interfaces, whose propagation is accompanied by development of large (comparable with the elastic modulus) tensile stresses. Abstract : Graphical abstract: fx1 Abstract : Highlights: A constitutive model is developed for swelling of thermo-responsive gels. Adjustable parameters are found by fitting observations in equilibrium and transient tests. Two scenarios of water release in T-jump tests are revealed by numerical simulation.